2002
DOI: 10.1093/pcp/pcf119
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Carboxyl Methyltransferase Induced in Hairy Root Cultures of Atropa belladonna after Treatment with Exogeneously Added Salicylic Acid

Abstract: ;In Atropa belladonna hairy roots, exogeneously added salicylic acid (SA) is converted to methyl salicylate (MSA) through the reaction, which might be catalysed by Sadenosyl-L-methionine: salicylic acid carboxyl methyltransferase (SAMT). Here we cloned a cDNA for A. belladonna SAMT (AbSAMT1), which consisted of 357 aa residues. It was expressed in E. coli, and the recombinant AbSAMT1 showed SAMT activity. When A. belladonna hairy roots were exposed to a high concentration of SA, AbSAMT1 mRNA begins to be expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…The A. belladonna SAMT gene was isolated and characterized in the cultured hairy roots of A. belladonna after exogenous SA had been administered (Fukami et al 2002). In the present study, AbSAMT1 was induced by exogenous SA in A. belladonna plants as well as in cultured hairy roots (Figure 1).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The A. belladonna SAMT gene was isolated and characterized in the cultured hairy roots of A. belladonna after exogenous SA had been administered (Fukami et al 2002). In the present study, AbSAMT1 was induced by exogenous SA in A. belladonna plants as well as in cultured hairy roots (Figure 1).…”
Section: Discussionsupporting
confidence: 52%
“…A. belladonna SAMT1 (AbSAMT1) (GenBank accession number: AB049752) showed that the expression of the AbSAMT1 gene was activated when exogenous SA was added to a medium containing cultured hairy roots of A. belladonna (Fukami et al 2002). In the present study, AbSAMT1 was expressed when A. belladonna was treated with exogenous SA, pathogens or 1,2-benzisothiazole-1,1-dioxide (BIT), by activating SAR as the chemical inducer.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…6) suggests that SAMT-expression is dependent on JA, similar to MeJA-inducible AtBSMT1 expression in Arabidopsis (Chen et al, 2003). However, in Atropa belladonna root cultures, SAMT appeared SA-inducible (Fukami et al, 2002). We were able to confirm the JA-dependency, since treatment of def-1 with JA resulted in enhanced spider miteinduced SAMT transcription (Fig.…”
Section: Ja Is Involved In Mesa and Tmtt Emissionmentioning
confidence: 54%
“…The snapdragon BA methyltransferase (BAMT) showed activity with BA but not with SA, although the K m -value for the physiological substrate BA, 1.1 mM , is considerably higher than the reported K m -values for SAMTs using SA, which range from 24 to 83 mM. So far, no SAMT or BAMT enzymatic activities in these species have been detected in organs other than¯owers (a putative SAMT, with a poorly characterized substrate speci®city, was reported to be induced in hairy root cultures of Atropa belladonna upon SA treatment; Fukami et al (2002)). Speci®cally, neither the expression of SAMT and BAMT could be detected in leaves under normal conditions, nor was the expression of SAMT and BAMT induced in leaves by various treatments, including administration of SA or methyljasmonate (MeJA; Negre et al, 2002;Ross, 2002).…”
Section: Introductionmentioning
confidence: 73%